Comparison of heat exchanger designs for ship ballast water heat treatment system - Balaji, R.; Yaakob, O.; Koh, K.; Adnan, F.; Ismail, N.; Ahmad, B.; Ismail, Mohamed; Vern, Y. (Penerbit Universiti Teknologi Malaysia, 2015)
Sterilisation by heat can be a capital treatment for ballast water and waste heat from ship’s engines will be a good resource. Based on the waste heat availability on an operational tanker, a ballast water treatment system was envisaged including a shipboard heat exchanger for waste heat recovery. To verify the heat availability and the species’ mortalities, test rigs were arranged similar to shipboard arrangement. For assessing the smaller heat exchangers for the tests, designs were developed using Bell-Delaware approaches based on the shipboard heat exchanger design. The thermodynamic and geometric values were computed and the features of the commercially available and fitted heat exchangers were compared with the developed designs. Two commercially procured heat exchangers fitted on two separate engine test rigs were used for tests. The designs of commercially procured heat exchangers were close to the developed designs and were found to be suitable for the tests planned.